Makna Khusyu’ Dalam Al-Qur’an: Studi Kajian Tematik Dalam Prespektif Tafsir Al-Azhar - A.Amirul Faizin, Faiz; Arif Firdausi N.R; Edy Wirastho (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2024)
This research focuses on Al-Azhar's interpretation of the concept of "khusyū" in the Quran in depth and comprehensively. It is based on literature review utilizing various books available in both physical and digital libraries that are easily accessible. The importance of this research lies in understanding the various meanings of khusyū found in Al-Azhar's interpretation and maximizing the quality of worship by understanding the science of khusyū in worship. The result of this research is the meaning of khusyū in Al-Azhar's interpretation, which refers to submission and total focus in worship, originating from the heart and manifested in both physical and spiritual forms during prayer. This includes lowering the gaze, keeping the body still, feeling tranquility, and dedicating oneself during worship. The word "khusyū" is also mentioned in the Quran in various contexts, both with positive meanings, such as worship and obedience to Allah, and with negative meanings, such as showing regret on the Day of Judgment for those who ignore Allah's warnings and engage in evil deeds. Khusyū serves as a primary indicator of one's faith and piety in Islam, and it is also the key to achieving happiness and salvation in both this world and the hereafter.